Thin Layer Chromatography - Direct Bioautography and Identification of Compounds from the Semi-purified Fraction of Senna alata (Linn.) - Scholastica Ramih, Bunya; Samuel, Lihan (Natural Product Research group, University of Beni, 2025)
The availability and affordability of medicinal plants, along with the fact that certain bacteria are resistant to synthetic drugs, have led to increased interest in natural products derived from plants for medical applications. Senna alata (Linn.), commonly known as “gelenggang” and “daun kurap”, has demonstrated a wide range of antibacterial properties against infections caused by bacterial pathogens. This study aimed to isolate and identify the bioactive compounds present in the leaf, stem, and root of Cassia alata, and to evaluate their antimicrobial activities. Thin Layer Chromatography-Direct Bioautography (TLC-DB) and Gas Chromatography-Mass Spectrometry (GC-MS) techniques were utilized for compound separation and identification. In the TLC separation, four, seven, and five spots were observed on the TLC plates for the leaf, stem, and root extracts, respectively. The bacterium Mammaliicoccus sp. exhibited a strong inhibition zone corresponding to one distinct spot on each TLC-DB plate: leaf (Rf = 0.47), stem (Rf = 0.40), and root (Rf = 0.42). In contrast, Enterococcus sp. showed a weaker inhibition at those same spots. GC-MS analysis of the active spots identified major bioactive compounds, including Phenol, 3,5- bis(1,1-dimethylethyl)-, Cholest-5-en-3-ol (3.beta.)-, carbonochloridate, Neophytadiene, Dodecane, 2,6,11-trimethyl-, 2-Pentadecanone, 6,10,14-trimethyl-, and Decane, 3,7-dimethyl-,.These findings suggest that Senna alata contains bioactive compounds with notable antimicrobial properties, supporting its potential application in developing alternative treatments for infections caused by Mammaliicoccus sp. and Enterococcus sp. This study highlights the importance of further investigating plan